Madborgerskab? Når videnskab møder hverdagspraksis - Halkier, Bente (Politik, 2014)
Food is an ordinary practice in everyday life. At the same time, food practices become politicised through at- tempts to regulate food related collective problems such as health, risk and climate by way of encouraging self- disciplining and normative regulation of everyday habits among citizens. Such regulatory technologies cover medialised change communication, and in the food eld, such communication often builds upon scienti c knowledge and arguments. us, when citizens relate to such communication, links between complicated scienti c knowledges and everyday translations are produced. Building on a practice theoretical approach, the article shows three empirically based ways in which Danish citizens handle scienti cally based change communication on food in their daily lives: Empowerment, resistance towards disciplining, and do-ability. e typology demonstrates that citizenship in the scienti cally based politicised food eld – „food-izenship“ – is more varied and compound than presumed in the existing approaches to change communication and the Public Understanding of Science literature.